Unique Fixed-Point Results in Fuzzy Metric Spaces with an Application to Fredholm Integral Equations. (23rd September 2021) - Shamas, Iqra; Rehman, Saif Ur; Aydi, Hassen; Mahmood, Tayyab; Ameer, Eskandar
Abstract : This paper aims at proving some unique fixed-point results for different contractive-type self-mappings in fuzzy metric spaces by using the "triangular property of the fuzzy metric". Some illustrative examples are presented to support our results. Moreover, we present an application by resolving a particular case of a Fredholm integral equation of the second kind.